Correlation-based assessment of 4G LTE network performance during rainfall events in tropical regions - Ngozi C. Eli-Chukwu; Uma Uzubi Uma; Handel Emezue; Ogechi Akudo Nwogu; Ogah E. Oga; Calister N. Ogbonna-Mba; Samuel I. Ezichi (Institute of Advanced Engineering and Science, 2026)
This paper presents a performance evaluation of a fourth-generation (4G) cel lular network under adverse weather conditions in a tropical region. While the impact of rainfall on frequencies above 10 GHz is well documented, this study addresses the research gap concerning 4G LTE performance (sub-6 GHz) in high-precipitation environments such as Nigeria. Using a drive-test approach with TEMS Investigation software (v16.3), measurements were collected over 48 days between July and September 2025 along a fixed 15 km route in the Lagos metropolis on the MTN Nigeria network. Samples were recorded at 1 second intervals. Four critical key performance indicators (KPIs)—reference signal received power (RSRP), reference signal received quality (RSRQ), signal to-interference-plus-noise ratio (SINR), and received signal strength indicator (RSSI)—wereanalyzedtodeterminetheir influence on the network performance index (NPI). Correlation analysis revealed that while RSRP exhibits no sig nificant correlation with NPI during rainfall (rs = 0.009), SINR and RSRQ demonstrate strong positive correlations (rs = 0.828 and rs = 0.824, respec tively). Despite these high correlations, average performance values remained low (mean SINR = 23.72%), indicating significant rain-induced degradation. These findings provide a novel empirical basis for the development of weather aware adaptive algorithms in tropical 4G network deployments.